2021
DOI: 10.52965/001c.24508
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and its psychological impact among healthy Portuguese and Spanish nursing students

Abstract: Health Psychology ResearchFew studies have explored the impacts of COVID-19 and lockdown on the mental health of undergraduate nursing students. This study aimed: a) to explore perceived stress among undergraduate nursing students in Portugal and Spain during the COVID-19 pandemic outbreak; and b) to analyze several COVID-19 related factors and psychological issues that may be associated with perceived stress. A cross-sectional study was conducted with a convenience sample of Portuguese and Spanish undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…Other factors were associated with the students’ experience of stress, such as the concern that they themselves (x = 3.15) or a family member (x = 4.51) might become infected with COVID-19. This concern has already been identified in other studies ( Laranjeira et al, 2021 ; Sui, Gong, & Zhuang, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
“…Other factors were associated with the students’ experience of stress, such as the concern that they themselves (x = 3.15) or a family member (x = 4.51) might become infected with COVID-19. This concern has already been identified in other studies ( Laranjeira et al, 2021 ; Sui, Gong, & Zhuang, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
“…Another study has shown an association between the consumption of sugary and carbonated drinks and fast food, and sleeping disorders due to anxiety in adolescents (Khan & Uddin, 2020). Laranjeira et al (2021) also shown an association between psychological impact and excess consumption of junk food. However, the association between increased anxiety and the consumption of coffee and stimulating drinks could just be a consequence of this consumption.…”
Section: Discussionmentioning
confidence: 95%
“…Restrictions due to the pandemic delayed numerous clinical teachings and consequently the development/completion of courses, further aggravating the students’ signs of distress. The rapid changes imposed upon higher education students, from the suspension of classes to the declaration of a state of emergency, triggered difficulties in adaptation and less positive emotional states [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Maia and Dias [ 39 ] explored the levels of anxiety, depression, and stress in Portuguese university students, indicating a significant increase in psychological disturbance during the pandemic period (between suspension of classes and the declaration of a state of emergency in Portugal) compared to normal periods. Another study with students from six higher education institutions in Portugal and Spain, during May 2020, found high perceived stress scores (51.4%) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%